Assessing hydrological connectivity of wetlands by dye-tracing experiment. (December 2020) - Dai, Liyi; Zhang, Yinghu; Liu, Ying; Xie, Lumeng; Zhao, Shiqiang; Zhang, Zhenming; Xizhi, Lv
Highlights: Quantifying hydrological connectivity with soil-profile indexes. Judging intensity of hydrological connectivity through dye pattern images. It is hydrological barrier making dye coverage increase at 10–20 cm deep. Hydrological connectivity weakens non-linearly from 10–20 cm deep. Dye-tracing experiments cannot fully indicate water movements in soil. Abstract: In order to provide useful and effective reference indicators for wetland protection and restoration, we are trying to understand the role of hydrological processes in wetlands with hydrological connectivity. To quantify hydrological connectivity at soil-profile scale with the soil-profile indexes, dye-tracing field tests were conducted in Yellow River Delta to determine the size and distribution of soil pores, as well as the trail of waterflow. After data analyses, the results showed: (1) where preferential pathways were rich, that is, where hydrological connectivity was strong, the dye coverage was larger (the dye coverage of CLa1 was 0.20 ± 0.08, when CLa2 was 0.22 ± 0.05 and CLa3 was 0.13 ± 0.02), and the dye coverage of preferential pathway was larger (the dye coverage of preferential pathway of CLa1 was 0.16 ± 0.07, when CLa2 was 0.19 ± 0.04 and CLa3 was 0.11 ± 0.02). (2) hydrological connectivity weakens non-linearly from about 30 cm deep. (3) hydrological barrier in soil made dye coverage increase at 10–20 cm deep and it would weaken the vertical hydrological connectivity and strengthen the horizontal hydrological connectivity by preventing the flow from infiltrating further down.